Diagnostic Ambiguity Caused by an Atypical e18a2 BCR::ABL1 Transcript in a Chronic Myeloid Leukemia Patient - Thomas Pretzsch; Steve Progscha; Thomas Burmeister (Case Reports in Hematology)
We describe the case of a chronic myeloid leukemia (CML) patient with a rare atypical e18a2 BCR::ABL1 transcript. The generation of this transcript was explained by a detailed molecular analysis, including the identification of both chromosomal breakpoints (BCR::ABL1 on der(22) and ABL1::BCR on der(9)) at the genomic level. The use of a cryptic splice site in intron 1 of ABL1 led to the generation of an in-frame BCR::ABL1 fusion transcript. The diagnostic difficulties caused by this atypical variant and its implications for diagnostic routine are discussed.